A study on personality traits and shopping online - Usakli, Hakan (Management and Administration Journal, 2020)
The aim of the article is to analyze inter- relations between online shopping behaviour and personality traits. Online shopping has been developing all over the world. People not only buy locally but also trade internationally via the internet. The method of the study is correlation with the use of SPSS programme. Two different inventories were administrated to 243 university students via online. Big-Five Personality Questionnaire and Compulsive Online Shopping Behaviour were used. This test apparatus indicates five different personality dimensions such as extraversion, agreeableness, conscientiousness, emotional stability, intellect imagination. The compulsive online shopping behaviour was applied to get data on online shopping. The findings indicate that there are correlations between personality traits and excessive online shopping behaviour. People who are less agreeable and self conscious should think more before shopping online.